Critical review of RDoC approaches to the study of motivation with animal models: effort valuation/willingness to work. Issue 5 (9th December 2022) - Salamone, John D.; Correa, Merce
Abstract : The NIMH research domain criteria (RDoC) approach was instigated to refocus mental health research on the neural circuits that mediate psychological functions, with the idea that this would foster an understanding of the neural basis of specific psychiatric dysfunctions (i.e. 'symptoms and circuits') and ultimately facilitate treatment. As a general idea, this attempt to go beyond traditional diagnostic categories and focus on neural circuit dysfunctions related to specific symptoms spanning multiple disorders has many advantages. For example, motivational dysfunctions are present in multiple disorders, including depression, schizophrenia, Parkinson's disease, and other conditions. A critical aspect of motivation is effort valuation/willingness to work, and several clinical studies have identified alterations in effort-based decision making in various patient groups. In parallel, formal animal models focusing on the exertion of effort and effort-based decision making have been developed. This paper reviews the literature on models of effort-based motivational function in the context of a discussion of the RDoC approach, with an emphasis on the dissociable nature of distinct aspects of motivation. For example, conditions associated with depression and schizophrenia blunt the selection of high-effort activities as measured by several tasks in animal models (e.g. lever pressing, barrier climbing, wheel running). Nevertheless, these manipulations also leave fundamental aspects of hedonic reactivity, food motivation, and reinforcement intact. This pattern of effects demonstrates that the general emphasis of the RDoC on the specificity of the neural circuits mediating behavioral pathologies, and the dissociative nature of these dysfunctions, is a valid concept. Nevertheless, the specific placement of effort-related processes as simply a 'sub-construct' of 'reward processing' is empirically and conceptually problematic. Thus, while the RDoC is an excellent general framework for new ways to approach research and therapeutics, it still needs further refinement.